Systemic ST6Gal-1 Is a Pro-survival Factor for Murine Transitional B Cells - Irons, Eric E.; Lau, Joseph T. Y. (Frontiers in Immunology, 2018)
Humoral immunity depends on intrinsic B cell developmental programs guided by systemic signals that convey physiologic needs. Aberrant cues or their improper interpretation can lead to immune insufficiency or a failure of tolerance and autoimmunity. The means by which such systemic signals are conveyed remain poorly understood. Hence, further insight is essential to understanding and treating autoimmune diseases and to the development of improved vaccines. ST6Gal-1 is a sialyltransferase that constructs the α2,6-sialyl linkage on cell surface and extracellular glycans. The requirement for functional ST6Gal-1 in the development of humoral immunity is well documented. Canonically, ST6Gal-1 resides within the intracellular ER-Golgi secretory apparatus and participates in cell-autonomous glycosylation. However, a significant pool of extracellular ST6Gal-1 exists in circulation. Here, we segregate the contributions of B cell intrinsic and extrinsic ST6Gal-1 to B cell development. We observed that B cell-intrinsic ST6Gal-1 is required for marginal zone B cell development, while B cell non-autonomous ST6Gal-1 modulates B cell development and survival at the early transitional stages of the marrow and spleen. Exposure to extracellular ST6Gal-1 ex vivo enhanced the formation of IgM-high B cells from immature precursors, and increased CD23 and IgM expression. Extrinsic sialylation by extracellular ST6Gal-1 augmented BAFF-mediated activation of the non-canonical NF-kB, p38 MAPK, and PI3K/AKT pathways, and accelerated tyrosine phosphorylation after B cell receptor stimulation. in vivo, systemic ST6Gal-1 did not influence homing of B cells to the spleen but was critical for their long-term survival and systemic IgG levels. Circulatory ST6Gal-1 levels respond to inflammation, infection, and malignancy in mammals, including humans. In turn, we have shown previously that systemic ST6Gal-1 regulates inflammatory cell production by modifying bone marrow myeloid progenitors. Our data here point to an additional role of systemic ST6Gal-1 in guiding B cell development, which supports the concept that circulating ST6Gal-1 is a conveyor of systemic cues to guide the development of multiple branches of immune cells.